Analysis of Income Attribution of Consumption Tax in China’s Central and Local Government - Yanguo Han; Wenchao Zhao; Haixia Hao; Xianfeng Zhang; Jingjing Zhou (Discrete Dynamics in Nature and Society)
After the policy to replace the business tax with a value-added tax was launched, local finance has encountered greater difficulties. In recent years, the economic downward pressure has made the dilemma far more serious. Some scholars, even from state level, showed some intentions of recommending that the consumption tax should be changed from the current central tax to a local tax or a shared tax to relieve the pressure of local governments. In this paper, we proved by presenting recent year’s tax figures of business, consumption, and local and central fiscals and their growth rate that replacing the consumption tax with a local tax does not exactly correspond to the trend of China’s reform of the financial system, the functional orientation of the consumption tax, and the nature of the consumption tax itself and may trigger some problems, and it may still be a better choice for the consumption tax to serve as a central tax.